Profile of regional fat and fat-free soft tissue accumulation in male athletes - Takai, Y.; Nakatani, M.; Aoki, T.; Komori, D.; Oyamada, K.; Murata, K.; Fujita, E.; Akamine, T.; Urita, Y.; Yamamoto, M.; Kanehisa, H. (Journal of Physiological Anthropology, 2020)
Background: It is unclear whether or not the breakpoint (BP), at which the proportion of each of fat mass (FM) and fat-free soft tissue mass (FFSTM) to body mass (BM) alter, exists in male athletes. We examined the hypothesis that in male athletes, the regional FM and FFSTM-BM relationships have a BP, but the body mass at BP (BMBP) differs among the arms, trunk, and legs. Methods:By using a dual X-ray absorptiometry, whole-body and regional FMs and FFSTMs in the arms, trunk, andlegs were estimated in 198 male athletes (20.8 ± 2.1 years; 1.73 ± 0.07 m; 72.7 ± 14.8 kg). To detect the BP in the relationship between each of FM and FFSTM and BM, a piecewise linear regression analysis was used. If a BP was detected in the corresponding relationship, the significant difference between the regression slopes above and below the BP was examined. Results:The regression analysis indicated that the BMBP existed in the FM- and FFSTM-BM relationships regardlessof region and whole body. For the whole body, BMBPwas 81.8 kg for FM and 82.2 kg for FFSTM. In regional FM-BM relationships, BMBP was 80.5 kg for arms, 82.6 kg for trunk, and 63.3 kg for legs, and the regression slopes above the BMBP became higher than those below the BP, and vice versa in regional FFSTM-BM relationships (BMBP104.6 kg forarms, 80.9 kg for trunk, and 79.0 kg for legs). The relative differences in the slopes between below and above BMBPin the regional FM-BM relationships were higher in the arms and trunk than in the legs, and those in the regional FFSTM-BM relationships in the legs than in the trunk. Conclusion: Whole-body and regional FM- and FFSTM-BM relationships for male athletes have breakpoints atwhich the proportion of the tissue masses to BM alters. The BMBP and differences in the distribution of regional FMand FFSTM around the breakpoint are region specific.